2011
DOI: 10.3390/rs3050962
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Sensor Approach to Examining the Distribution of Total Suspended Matter (TSM) in the Albemarle-Pamlico Estuarine System, NC, USA

Abstract: For many coastal waters, total suspended matter (TSM) plays a major role in key biological, chemical and geological processes. Effective mapping and monitoring technologies for TSM are therefore needed to support research investigations and environmental assessment and management efforts. Although several investigators have demonstrated that TSM or suspended sediments can be successfully mapped using MODIS 250 m data for relatively large water bodies, MODIS 250 m data is of more limited use for smaller estuari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Second, as the use of MODTRAN makes it possible to simulate the spectral response of atmospheric molecules and aerosols at extremely high spectral resolution, FLAASH can be applied to a variety of multispectral satellite sensors. For example, FLAASH was used for a MODIS/Landsat/Formosat study of SPM distribution in a US estuarine system [29], and for the analysis of benthic microalgae spatial interactions using long-term Landsat and SPOT time-series in an intertidal ecosystem [52]. The present study confirmed the efficiency of FLAASH for the processing of hyperspectral airborne data as well as MERIS multispectral satellite data, and FLAASH can be equally applied to many other airborne and satellite sensors.…”
Section: Other Advantages Of Flaashsupporting
confidence: 56%
See 1 more Smart Citation
“…Second, as the use of MODTRAN makes it possible to simulate the spectral response of atmospheric molecules and aerosols at extremely high spectral resolution, FLAASH can be applied to a variety of multispectral satellite sensors. For example, FLAASH was used for a MODIS/Landsat/Formosat study of SPM distribution in a US estuarine system [29], and for the analysis of benthic microalgae spatial interactions using long-term Landsat and SPOT time-series in an intertidal ecosystem [52]. The present study confirmed the efficiency of FLAASH for the processing of hyperspectral airborne data as well as MERIS multispectral satellite data, and FLAASH can be equally applied to many other airborne and satellite sensors.…”
Section: Other Advantages Of Flaashsupporting
confidence: 56%
“…In nearshore areas, FLAASH has been successfully applied to airborne remote sensing over tidal flats [27,28], but has received little attention so far for ocean color remote sensing. Due to the very high resolution of MODTRAN atmospheric spectral libraries, FLAASH is applicable to a wide range of multispectral satellite sensors [29], including MERIS. The aim of the present study is to evaluate the accuracy of FLAASH for MERIS observation in a turbid coastal zone.…”
Section: Study Sitementioning
confidence: 99%
“…In coastal and estuarine environments, total suspended matter (TSM) plays a significant role in physical, biological, and chemical processes (Miller et al, 2011). A unique feature of Minas Basin is that biological community structure and trophic pathways seem to be controlled by dynamics of suspended sediment.…”
Section: List Of Figuresmentioning
confidence: 99%
“…The dynamic nature of estuarine systems necessitates finer-scale monitoring, both temporally and spatially. Remote sensing can help overcome the weaknesses of in situ sampling by providing comprehensive spatial and consistent temporal coverage [17].…”
Section: Introductionmentioning
confidence: 99%